“Everyone Knows What Wańkowicz Is Like.” What Did Czesław Miłosz, Jerzy Giedroyc and Others Know? - Szczęsna, Justyna (Porównania, 2025)
In Czesław Miłosz's The History of Polish Literature, the name of Melchior Wańkowicz is left unsaid. What were the reasons behind this omission? How did Miłosz himself comment on it, and how - Jerzy Giedroyc? What was hiding behind the concise "We know what Wańkowicz is like"? What did Miłosz and Giedroyc really know? The history of Wańkowicz and Giedroyc's acquaintance is reconstructed here in the context of their correspondence and Giedroyc's autobiography. The text answers the question why at the beginning of Kultura (Culture) Wańkowicz was one of its closest collaborators and why, after the success of Klub Trzeciego Miejsca (The Third Place Club), Kultura practically lost interest in him. The second important thread is the correspondence with Miłosz initialized by Wańkowicz in 1951. How did they perceive the emigration experience? How did they view the post-war choices? How did they differ? The third perspective taken here is Wańkowicz as told by Maria Dąbrowska in Dzienniki (Journals). How did an emigrant returning to his country impress Dąbrowska?